Adapting Levels 1 and 2 of Kirkpatrick's model of training evaluation to examine the effectiveness of a tertiary-level writing course. (3rd April 2017) - Aryadoust, Vahid
ABSTRACT: This study adapts Levels 1 and 2 of Kirkpatrick's model of training evaluation to evaluate learning outcomes of an English as a second language (ESL) paragraph writing course offered by a major Asian university. The study uses a combination of surveys and writing tests administered at the beginning and end of the course. The survey evaluated changes in students' perception of their skills, attitude, and knowledge (SAK), and the writing tests measured their writing ability. Rasch measurement was applied to examine the psychometric validity of the instruments. The measured abilities were successively subjected to path modeling to evaluate Levels 1 and 2 of the model. The students reported that the module was enjoyable and useful. In addition, their self-perceived level of skills and knowledge developed across time alongside their writing scores but their attitude remained unchanged. Limitations of Kirkpatrick's model as well as lack of solid frameworks for evaluating educational effectiveness in applied linguistics are discussed.